Effect of Pt on the microstructure and oxidation behavior of NiCrAlYSi+AlY coating on a Ni-based superalloy. (January 2022) - Xiao, H.; Sun, J.; Li, W.; Liu, S.B.; Fu, L.B.; Jiang, S.M.
Abstract: The NiCrAlYSi+Al, NiCrAlYSi+AlY and Pt modified NiCrAlYSi+AlY coatings were produced by combining arc ion plating, electroplating Pt and annealing treatment. Isothermal oxidation and cyclic oxidation behaviors of all coatings were investigated. The Pt modified NiCrAlYSi+AlY coating showed the best oxidation resistance because the Pt addition decreased the oxidation rate and Al consumption in the coating. The "oxide pegs" were observed at the interface between oxide scale and Pt modified NiCrAlYSi+AlY coating after cyclic oxidation. The formation mechanism of coating and the effects of Pt and Y addition on the oxidation performance of coating were discussed. Highlights: Pt modified coating can be produced by combining AIP, electroplating Pt and annealing treatment. The Pt modified coating showed the excellent resistance of oxide scale spallation. The "oxide pegs" were beneficial to improve the adhesion of oxide scale. The addition of Pt and Y decreased the oxidation rate.